Differences of plasma IL-1 and TNF-α in healthy Chinese Population - Yuan, Jintao (Open Med (Wars), 2015)
Pleiotropic proinflammatory cytokines, interleukin- 1 (IL-1) and tumor necrosis factor-α (TNF-α), involved in the regulations of various immune responses, inflammatory processes and hematopoiesis. In the present study, the expression levels of IL-1 and TNF-α were detected by enzyme-linked immunosorbent assay (ELISA). Following the cytokine blockade as a successful clinical therapy for autoimmune diseases such as rheumatoid arthritis, the patients are more susceptible to a variety of opportunistic infections. IL-1 and TNF-α may be useful predictive biomarkers of diseases and offer potential targets for therapeutic intervention of inflammatory diseases. However, our results showed that the plasma IL-1 level was significantly higher in women compared to men (69.5 ± 19.8 pg/ml in men and 80.1 ± 19.5 pg/ml in women, respectively); the plasma levels of TNF-α were higher in men than women (20.8 ± 4.9 pg/ml and 18.7 ± 7.1 pg/ml, respectively). The significant gender difference of plasma interleukin-1 (IL-1) and TNF-α levels present in healthy adults in Jiangsu Province, China (P=0.002 and P=0.015, respectively), and may be as a hint for sex differences of susceptibility to many diseases and elementary immune response.